A novel membrane bioreactor for detoxifying industrial wastewater: I. Biodegradation of phenol in a synthetically concocted wastewater. - Livingston,AG (Biotechnol Bioeng, 1993)
A novel process has been used to biodegrade phenol present in an acidic (1 M HCI) and salty (5% w/w NaCl) synthetically bioreactor, in which the phenol present in the wastewater is separated from the inorganic components by means of a silicone rubber membrane. Transfer of the phenol from the wastewater and into a biological growth medium allows biodegradation to proceed under controlled conditions which are unaffected by the hostile inorganic composition of the wastewater. At a wastewater flow rate of 18 mL h(-1) (contact time 6 h), 98.5% of the phenol present in the wastewater at an inlet concentration of 1000 mg ((-1)) was degraded; at a contact time of 1.9 h, 65% of the phenol was degraded. Phenol degradation was accompanied by growth of a biofilm on the membrane tubes and by conversion of approximately 80% of the carbon entering the system to CO(2) carbon. Analysis of the transport of phenol across the membrane revealed that the major resistance to mass transfer arose in the diffusion of phenol across the silicone rubber membrane. A mathematical model was used to describe the transfer of phenol across the membrane and the subsequent diffusion and reaction of phenol in the biofilm attached to the membrane tube. This analysis showed that (a) the attached biofilm significantly lowers the mass transfer driving force for phenol across the membrane, and (b) oxygen concentration limits the phenol degradation rate in the biofilm. These conclusions from the model are consistent with the experimental results.